Study of Household Environmental Sanitation Risk Factors on Stunting Incidence in Toddlers in Dongos Village, Kedung I Health Center Working Area, Jepara Regency - Wakhid Anwar; Nurjazuli; Tri Joko (Postgraduate, University of Mataram, 2025)
Stunting is a condition of linear growth disorders due to chronic lack of intake and occurs in many developing countries including Indonesia. Stunting is a problem because it is associated with an increased risk of illness and death, suboptimal brain development so that motor development is delayed and mental growth is inhibited, this can hinder the Indonesian government's program towards a superior and quality golden generation in 2045. The purpose of this study was to determine the risk factors for household environmental sanitation on the incidence of stunting in toddlers in Dongos Village, Kedung I Health Center, Jepara Regency. This study is an observational analytical study using a quantitative method with a case-control study design, namely a study comparing case and control groups and then retrospectively examining risk factors that might explain the incidence of stunting. The study sample was stunted and non-stunted toddlers, calculated using lemmeshow formula with the absolute accuracy proportion estimate with a total sample of 100 respondents divided into 50 case groups and 50 control groups. Data analysis with Chi Square test then further using logistic regression test using prediction modeling. The results of the study showed that unsafe household waste management has a risk factor of 3.6 times greater for stunting in toddlers (p-value 0.029; Odds Ratio = 3.632; 95% CI = 1.082- 12.183). Houses with unsafe household waste management have a 5.2 times greater risk of experiencing stunting in toddlers (p-value 0.025; Odds Ratio = 5.268; 95% CI = 1.077- 25.779). Household toilet ownership (p value = 0.400) and household drinking water consumption patterns (p value = 0.338) were not proven to be risk factors for stunting in toddlers in Dongos Village, Kedung I Health Center working area, Jepara Regency.